The Menance of Type 2 Diabetes to Anxiety and Depression Prevalence (Indian Journal of Public Health Research & Development, 2022)
Objectives: To estimate the prevalence of anxiety and depression using the Hospital Anxiety and Depression Scale (HADS) in a population aged over sixty years with type 2 diabetes and to study the impact of anxiety and depression on glycemic balance and disease outcome. Results: The prevalence of anxiety and depression in the 62 subjects included in the study was, respectively, 40.3% and 22.6%. We found a relationship between these disorders and complicated diabetes. The subjects having an imperfectly balanced diabetes had a higher average anxiety score than those having a good glycemic control (9.1 ± 4.2 versus 6.5 ± 3.1; P = 0.017). No relationship was found between diabetes balance and depression. Conclusion: Association between anxiety and depressive disorders and diabetes is frequent and worsens patients’ outcome, in terms of diabetes imbalance as well as in terms of diabetic complications. Our study shows that there is need for physicians to detect, confirm, and treat anxiety and depressive disorders in elderly diabetic patients
Keywords: : anxiety, depression, diabetic, scale